Huge Lipoma of Left Parotid Region with Intra-Parotid Extension - Amatya, N; KC, AK; Shrestha, BL; Shrestha, KS (Kathmandu University Medical Journal, 2023)
Lipoma is a benign mesenchymal tumor originating from adipose tissue. The occurrence of this tumor in head and neck is less frequent and it rarely involves parotid gland. These are asymptomatic and occur both in the deep and the superficial lobe of the parotid. The most favored age group is from the fifth to sixth decade of life and is 10 times more common in the males.A 66-year-old male patient, with left parotid region lipoma is reported in this article. A fine-needle aspiration biopsy and ultrasonography were performed to establish the preoperative diagnosis and to plan the correct surgical approach. It was managed by surgical excision of lipoma with removal of cuff of superficial parotid tissue on superior aspect with preserving facial nerve. Follow-up examinations were planned to assess any facial nerve injury complications.